Has the clinical governance development agenda stalled? Perceptions of New Zealand medical professionals in 2012 and 2017. Issue 2 (February 2020) - Gauld, Robin; Horsburgh, Simon
Highlights: Longitudinal study of medical professional perceptions of clinical governance development. The survey method permitted investigation of perceptions at two points in time. Study shows clinical governance development appears to have stalled, despite government policy. Study has implications for other countries where clinical governance is a core policy. Abstract: Clinical governance is a key policy and organisational foundation for health care quality improvement. This study sought to measure progress with clinical governance development from the perspective of practicing medical professionals in the New Zealand public health system. A short fixed-response survey, with questions derived from a government policy statement, was sent in 2012 and 2017 to all registered medical professionals in ongoing employment in New Zealand's public health system. Respondents, therefore, worked across New Zealand's 20 District Health Boards (DHBs), which own and manage public hospital and health care services. The survey sought to gauge medical professionals' perspectives around performance on, and implementation of, key clinical governance components. The overall performance in clinical governance development declined or stalled between the two survey periods across eight out of 10 key survey questions. There were improvements on two questions relating to respondent familiarity with clinical governance concepts, and to management support for clinical leadership development, but no change in areas such as having a structure to support clinical governance, or working in partnership with management. Limited government and DHB policy attention to clinical governance may well have contributed to stalled development across the New Zealand health system. If so, this finding has lessons for other countries and health systems in which there has been varying government support for the clinical governance agenda with ramifications around expectations for clinical leadership on, and involvement in, quality improvement.